1997
DOI: 10.1038/sj.hdy.6881320
|View full text |Cite
|
Sign up to set email alerts
|

Correlated variation of chiasma frequency and synaptonemal complex length in Locusta migratoria

Abstract: Mean diplotene chiasma frequency is shown to be significantly and positively correlated with mean synaptonemal complex (SC) length in 21 males of Locusta migratoria belonging to three different families. This may reflect a direct causal connection between SC length and chiasma frequency or an indirect relationship arising from the action of other factors with effects on both parameters. Various interpretations of the correlation are discussed in the light of old and new information on synaptic and recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…This statement can now be extended to higher plants, since we obtained comparable results in A. thaliana. Such correlated variations in SC length and CO number were also reported among chromosomes in one sex only, among individuals in the same species, and even among meiocytes in a single organism [5,17,[47][48][49][50]. However, based on current knowledge it is difficult to claim that SC length determines CO number, if the reverse is true, or even if another unidentified factor determines both.…”
Section: Discussionmentioning
confidence: 83%
“…This statement can now be extended to higher plants, since we obtained comparable results in A. thaliana. Such correlated variations in SC length and CO number were also reported among chromosomes in one sex only, among individuals in the same species, and even among meiocytes in a single organism [5,17,[47][48][49][50]. However, based on current knowledge it is difficult to claim that SC length determines CO number, if the reverse is true, or even if another unidentified factor determines both.…”
Section: Discussionmentioning
confidence: 83%
“…One factor that has, however, been shown to influence the rate of meiotic recombination is the length of particular chromosome pairs in different cells. In the spermatocytes of grasshoppers and humans, measurement of chiasma positions along bivalents revealed that the lengths of these bivalents varied between cells and that this variation was positively correlated with chiasma frequency (Fox, 1973;Hultén, 1974;Quevedo et al, 1997). These earlier studies, however, were somewhat indirect as recombination could only be measured by chiasma analysis, i.e.…”
Section: Genomic Levels Of Recombinationmentioning
confidence: 94%
“…In fact, this phenomenon has been previously noticed by other authors in human and other organisms. 8,10,21 Recently, a covariation of SC length has been described. 9 By comparing two different sets of chromosomes, one with chromosomes displaying different physical size but similar genetic length (chromosomes 16 and 19) and the other with chromosomes of similar physical size but different genetic length (chromosomes 21 and 21), it has been found that SC length reflects genetic length instead of physical length of a concrete chromosome.…”
Section: Resultsmentioning
confidence: 99%